SISTEM INFORMASI GEOGRAFIS PERSEBARAN PONDOK PESANTREN DI KABUPATEN DEMAK TAHUN 2021 - Septiana Zuhro (CV. ADIBA AISHA AMIRA, 2024)
Islamic boarding schools as traditional Islamic educational institutions have an important role in forming community character and religious identity. As an area rich in Islamic history, Demak Regency is the focus of Islamic boarding school development. The aim of this research is to analyze and document the distribution of Islamic boarding schools in Demak Regency as well as the factors that influence the distribution and growth of Islamic boarding schools in the area. The research methodology uses a qualitative approach using data collection techniques such as field surveys, in-depth interviews with Islamic boarding school managers, and geospatial data analysis. Primary data was obtained through direct observation in the field and in-depth interviews with key stakeholders. Secondary data was obtained from official government sources, religious institutions, and related literature.